The effectiveness of applying social constructivism models in physics on the academic achievement of second year secondary school students in the Kingdom of Saudi Arabia - Alzahrani, Hanaa Atiyah (Journal of Educational and Psychological Sciences, 2022)
The research aimed at identify the impact of the effectiveness of applying social constructivism models in physics on the academic achievement of second-year secondary school students in the Kingdom of Saudi Arabia. To achieve this goal, the experimental approach based on quasi-experimental design was used. Generative learning, and put it in the form of the teacher’s guide and the student’s activity booklet, and then build the research tools, which are the academic achievement test, and apply them to the two research groups, which amounted to (68) female students from the second grade of secondary school, with (34) female students for the experimental group, who were studied using The generative learning model, and (34) female students of the control group, studied in the usual way, and the data were treated statistically. The results of the research showed that there were statistically significant differences at the level (α≤0.05) between the mean scores of the students of the experimental and control groups in the post application of the achievement test; Where the experimental group got a total average (28.15 out of 30), while the control group got an average (19.44 out of 30), and the total effect size on achievement was (0.66) with a significant degree of impact, and based on these results, a number of Among the recommendations and proposals that contribute to the development of teaching and learning physics.
Keywords: social constructivist theory; generative learning; academic achievement